PENGGUNAAN ALAT PERAGA SULINGPUSLING PADA MATERI SUDUT KELILING DAN SUDUT PUSAT LINGKARAN - Lilik Firdayati (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Objective of study was to determine students' learning pattern in understanding angle around the circle and center corner of the circle concepts through teaching aids' suling and pusling' and also to know students' activities at the instruction. The advantages of teaching aids is to motivate students learning, so that they will be more selfconfident in finding concrete mathematics concepts, moreover, the instructional activity will be more enjoyable. Research method was Research and Development(R and D). The result of study showed that 'suling ang pusling' teaching aids could ease students grabbed the concepts i.e the relation betwen angles around the circle and center corner of The circle. It was shown from observation sheet results of students activities that their activities through this teaching aids could be at very active level with average students' score 80.86%